(untitled) (Scientia Agropecuaria, 2023)
Drought is an extreme climatic event that generates large impacts and losses in agriculture, causing the increase of global food insecurity and unsustainability of rural livelihoods. Based on this, the objective of this research was to conduct a systematic review of empirical studies that have reported the relationship between risk perception and adaptive strategies of farmers in the face of drought. For this reason, the review followed the guidelines and recommendations of the PRISMA statement. The databases consulted were Web of Science, Scopus and EBSCO. In total, 50 empirical studies, in Spanish and English, published between 2010 and 2021, that met the selection criteria were reviewed. The results highlight thdifferent factors influencingisk perception (years of experience, level of schooling, among others) and adaptation strategies (farm size, gender, access to credit, etc.). Finally, the effects of drought at the crop, livestock, personal and environmental levels were identified. In conclusion, we discuss its implications and limitations, highlighting the absence of studies in the Latin American region and in Spanish language. Future studies should be done with a place-based perspective, under which adaptive knowledge, beliefs, practices and actions can be recognized. On the other hand, climate change mitigation policies and programs must be proposed and implemented at a local scale.